Inclusive values of sport activities - Arkadiusz Kaźmierczak (Journal of Education, Health and Sport, 2018)
The universal nature of sport, together with its positive impact on physical, emotional and social development, is an effective means of eliminating the stigma associated with disability. Sport identified as a phenomenon of modern culture and education, thanks to its unique character, refers to broadly understood humanism, significantly contributing to supporting socialization, independence, initiation and full integration. Sports activity along with the idea of Olympism and behavior in accordance with the established rules of "fair play" are also an alternative way for disabled people to gain faith in their own abilities, eliminate the effects of disability, or are an area of improving the quality of life and strengthening family and social ties. It seems obvious that in this context sport should not be elite, but should be characterized by the mass participation of disabled people in recreational and qualified sports activities.